Selection of resistance by antimicrobial coatings in the healthcare setting. Issue 1 (September 2020) - Pietsch, F.; O'Neill, A.J.; Ivask, A.; Jenssen, H.; Inkinen, J.; Kahru, A.; Ahonen, M.; Schreiber, F.
Summary: Antimicrobial touch surfaces have been introduced in healthcare settings with the aim of supporting existing hygiene procedures, and to help combat the increasing threat of antimicrobial resistance. However, concerns have been raised over the potential selection pressure exerted by such surfaces, which may drive the evolution and spread of antimicrobial resistance. This review highlights studies that indicate risks associated with resistance on antimicrobial surfaces by different processes, including evolution by de-novo mutation and horizontal gene transfer, and species sorting of inherently resistant bacteria dispersed on to antimicrobial surfaces. The review focuses on antimicrobial surfaces made of copper, silver and antimicrobial peptides because of the practical application of copper and silver, and the promising characteristics of antimicrobial peptides. The available data point to a potential for resistance selection and a subsequent increase in resistant strains via cross-resistance and co-resistance conferred by metal and antibiotic resistance traits. However, translational studies describing the development of resistance to antimicrobial touch surfaces in healthcare-related environments are rare, and will be needed to assess whether and how antimicrobial surfaces lead to resistance selection in these settings. Such studies will need to consider numerous variables, including the antimicrobial concentrations present in coatings, the occurrence of biofilms on surfaces, and the humidity relevant to dry-surface environments. On-site tests on the efficacy of antimicrobial coatings should routinely evaluate the risk of selection associated with their use.